2018
DOI: 10.1016/j.vaccine.2018.02.066
|View full text |Cite
|
Sign up to set email alerts
|

A safety and immunogenicity study of immunization with hVEGF26-104/RFASE in cynomolgus monkeys

Abstract: These data show that hVEGF/RFASE can be safely administered in cynomolgus monkeys, induces the desired immune response and therefore support the clinical development of this vaccine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…These mutations create a local conformational perturbation within the receptor binding domain of the antigen. Despite this, the polyclonal antibody response elicited after immunization blocks the receptor binding domain on natural VEGF as well as the binding site for antigen and RFASE as adjuvant [16]. This VEGF therapeutic vaccine has shown antiangiogenic and antitumor activity in pre-clinical models [15], but discrete results in terms of immunogenicity have been observed in the first cancer patients treated with the vaccine [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These mutations create a local conformational perturbation within the receptor binding domain of the antigen. Despite this, the polyclonal antibody response elicited after immunization blocks the receptor binding domain on natural VEGF as well as the binding site for antigen and RFASE as adjuvant [16]. This VEGF therapeutic vaccine has shown antiangiogenic and antitumor activity in pre-clinical models [15], but discrete results in terms of immunogenicity have been observed in the first cancer patients treated with the vaccine [17].…”
Section: Discussionmentioning
confidence: 99%
“…This antigen sequence represents the complete Bevacizumab binding site and using RFASE as adjuvant, the vaccine (hVEGF 26-104 /RFASE) induces an immune response with VEGF neutralizing activity and anti-tumor effect [15]. Elicited polyclonal antibody response in addition to its cross-reactivity with human VEGF, have also demonstrated in rats and monkeys its capacity to impair the binding of Bevacizumab to VEGF [15,16], indicating the presence of antibodies that block binding sites on VEGF which have shown to be clinically relevant. This vaccine is being investigated in a phase I open-label clinical trial (NCT02237638), and preliminary results of the first included patients indicated that hVEGF 26-104 /RFASE has a good safety profile.…”
Section: Introductionmentioning
confidence: 99%
“…The finding of the presence of bevacizumab-blocking antibodies within the polyclonal response elicited by CIGB-247 indicates that the specific humoral response is directed to relevant domains on VEGF. The induction of bevacizumab-blocking antibodies by active immunization has been also developed by Wentink et al This approach is based on vaccination against the bevacizumab binding site on VEGF using a truncated protein (human VEGF 26-104 ) as antigen and RFASE as adjuvant [21]. This VEGF therapeutic vaccine has shown antiangiogenic and antitumor activity in pre-clinical models [20], but discrete results in terms of immunogenicity have been observed in the first cancer patients treated with the vaccine [22].…”
Section: Uc-ha14mentioning
confidence: 99%
“…Using RFASE as adjuvant, the vaccine (hVEGF 26-104 /RFASE) induces an immune response with VEGF neutralizing activity and anti-tumor effect [20]. In rats and monkeys immunized with this vaccine candidate, the VEGFspecific polyclonal antibody response has also demonstrated its capacity to impair the binding of bevacizumab to VEGF, suggesting the presence of antibodies that target the same VEGF epitope as bevacizumab [20,21]. This vaccine is being investigated in a phase I open-label clinical trial (NCT02237638), and preliminary results of the first included patients indicated that hVEGF 26-104 / RFASE has a good safety profile.…”
Section: Introductionmentioning
confidence: 99%
“…It would offer the advantage of continuous and a potentially more pronounced inhibition of VEGF without the need for repeated antibody administrations. Here, we describe the results of a phase-I trial of the novel therapeutic vaccine hVEGF 26-104 /RFASE 1,2 in patients with advanced solid malignancies.…”
mentioning
confidence: 99%